PENGEMBANGAN MODUL BERBASIS DISCOVERY LEARNING DISERTAI NILAI KARAKTER BERBANTU QR CODE PADA MATERI PENCEMARAN LINGKUNGAN UNTUK SISWA KELAS X - Mely Diana Rosa; Muhfahroyin Muhfahroyin; Triana Asih (EDUBIOLOCK, 2022)
The purpose of this development research is to produce a product in the form of a discovery learning-based module with appropriate QR Code-assisted character values ​​so that it can be used by students and increase knowledge. This type of development research using 4D models initiated by Thiagarajan, Sammel and Sammel (1974). This 4D development model has four stages, namely define, design,develop and desseminate, but in development research it only reaches the develop stage. The product that has been developed by this researcher has been validated by design experts, getting a percentage of 93% with the "very good" criteria, material expert validation getting a presentation of 89% with the "very good" criteria, and small group trials getting a percentage of 82% with the "very good" criteria. ". Based on the results of expert validation and small group testing, the product that has been developed in the form of a module is suitable for use by students during the learning process